2013
DOI: 10.1587/transinf.e96.d.502
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Chat Noir is PSPACE-Complete

Abstract: SUMMARYWe study the computational complexity of the following two-player game. The instance is a graph G = (V, E), an initial vertex s ∈ V, and a target set T ⊆ V. A "cat" is initially placed on s. Player 1 chooses a vertex in the graph and removes it and its incident edges from the graph. Player 2 moves the cat from the current vertex to one of the adjacent vertices. Players 1 and 2 alternate removing a vertex and moving the cat, respectively. The game continues until either the cat reaches a vertex of T or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Recently, Block Sum [6], Kaboozle [2], Kurodoko [14], Magnet Puzzle [15], Pandemic [16], Pyramid [10], Shisen-Sho [13], String Puzzle [12], Yosenabe [9], and Zen Puzzle Garden [8] were shown to be NPcomplete. Furthermore, it is known that Chat Noir [11] and Rolling Block Maze [3] are PSPACE-complete.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Block Sum [6], Kaboozle [2], Kurodoko [14], Magnet Puzzle [15], Pandemic [16], Pyramid [10], Shisen-Sho [13], String Puzzle [12], Yosenabe [9], and Zen Puzzle Garden [8] were shown to be NPcomplete. Furthermore, it is known that Chat Noir [11] and Rolling Block Maze [3] are PSPACE-complete.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, a survey of games, puzzles, and their complexities was reported by Hearn and Demaine [4]. Recently, Block Sum [3], Pyramid [7], String Puzzle [9], Tantrix Match [10], Yosenabe [6], and Zen Puzzle Garden [5] were shown to be NPcomplete, and Chat Noir [8] is PSPACE-complete.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was also shown that Block Sum [8], Kaboozle [2], Magnet Puzzle [16], Pandemic [17], Shisen-Sho [14], String Puzzle [13], single-player UNO [5] and Zen Puzzle Garden [10] are NP-complete. As for higher complexity classes, Chat Noir [12], Rolling Block Maze [3], and two-player UNO [5] were shown to be PSPACE-complete.…”
Section: Introductionmentioning
confidence: 99%